Synthesis and Characterization of Zirconium Oxychloride from Bangka and Belitung Zircon Sand - Nurhadini Nurhadini; Verry Andre Fabiani; Sun Theo Constan Lotebulo Ndruru; Widodo Budi Kurniawan (Jurnal Kimia Sains dan Aplikasi, 2025)
Although zircon sand, a byproduct of tin mining in Bangka and Belitung, is abundant and rich in zirconium content, it remains underutilized despite its potential for conversion into value-added products. This study aims to explore the feasibility of using Bangka and Belitung zircon sand as raw materials for the synthesis and characterization of zirconium oxychloride octahydrate (ZrOCl2·8H2O), and to evaluate its properties relative to a commercial reference. A hydrometallurgical process involving alkaline fusion and acid leaching was employed to convert zirconium silicate (ZrSiO4) into ZrOCl2·8H2O. Comprehensive characterization was conducted using X-ray fluorescence, X-ray diffraction, Fourier-transform infrared spectroscopy, scanning electron microscopy, and particle size analysis. The results revealed that Bangka zircon sand contains a higher zirconium content (79.12%) than Belitung sand (76.97%). Both sources exhibited lower zirconium purity and higher chlorine content compared to a reference. Despite these limitations, the total Zr and Cl content reached 88.12% for the Bangka sample and 86.08% for the Belitung sample, indicating promising potential. Both products shared similar structural and morphological features in different sizes. Belitung-derived ZrOCl2·8H2O exhibited a higher ZrOCl2·8H2O phase, more defined morphology, and smaller size, suggesting it has better properties as a precursor in zirconium-based applications. This study supports the valorization of mining byproducts and highlights the potential of local zircon sand as a raw material for zirconium-based applications.